Carfilzomib, lenalidomide, and dexamethasone in relapsed refractory multiple myeloma: a prospective real-life experience of the Regional Tuscan Myeloma Network - Antonioli, Elisabetta; Pilerci, Sofia; Attucci, Irene; Buda, Gabriele; Gozzetti, Alessandro; Candi, Veronica; Simonetti, Federico; Giudice, Maria Livia Del; Ciofini, Sara; Staderini, Michela; Grammatico, Sara; Buzzichelli, Alessandra; et al. (Frontiers in Oncology, 2023)
Introduction Carfilzomib, a potent, irreversible, selective proteasome inhibitor has demonstrated consistent results in relapsed/refractory multiple myeloma (RRMM) combined with lenalidomide and dexamethasone (KRd). No prospective studies are yet available that analyzed the efficacy of the KRd combination. Methods Herein, we report a multicenter prospective observational study on 85 patients who were treated with KRd combination as the second or third line of treatment, according to standard practice. Results The median age was 61 years; high-risk cytogenetic was found in 26% and renal impairment (estimated glomerular filtration rate (eGFR) <60 ml/min) in 17%. After a median follow-up of 40 months, patients received a median number of 16 cycles of KRd, with a median duration of treatment (DoT) of 18 months (range, 16.1–19.2 months). The overall response rate was 95%, with a high-quality response (≥very good partial remission [VGPR]) in 57% of the patients. The median progression-free survival (PFS) was 36 months (range, 29.1–43.2 months). Achievement of at least VGPR and a previous autologous stem cell transplantation (ASCT) were associated with longer PFS. The median overall survival (OS) was not reached (NR); the 5-year OS rate was 73%. Nineteen patients underwent KRd treatment as a bridge to autologous transplantation, obtaining a post-transplant minimal residual disease (MRD) negativity in 65% of cases. The most common adverse events were hematological, followed by infection and cardiovascular events, rarely G3 or higher, with a discontinuation rate for toxicities of 6%. Our data confirmed the feasibility and safety of the KRd regimen in real life.